Crystal bones. A case report - Alexander Torres Molina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
There is a case still on milk with clinical and radiological manifestations with the diagnosis of imperfect osteogenesis. There was a study with the clinical description of the external habit, detecting triangular facie, slight blue sclera, ligamentous hypelaxitud in hands and feet, pectus excavatum, arrosariated ribs, legs in abduction, keeping a right angle and diafisiary fractures of long bones. The parents clinical study was normal. The typification was according Sillence criteria of Type III.